MENINGKATKAN HASIL BELAJAR POLINOMIAL MELALUI METODE OUTDOOR DAN INDOOR BERSISTEM SEPUR SELAM - Nikken Isnaini Hidayah; Vina Dwi Riski; Lela Kumalasari (Jurnal Pembelajaran Matematika, 2018)
Abstract: One of the successful indicators in mathematics learning is marked by achievement of optimal learning outcomes. However, students' mathematics learning outcomes in several districts in Indonesia are still low. This is proved by the decline of national examination average score in mathematics subjects. The average national exam results of Senior High School at Sukoharjo District decrease from 2016 to 2017, namely 12,92% from 56.59 into 49.28. One of the factors that cause the problem is students are less motivated in participating learning process because material presentation by teachers is less attractive. This study aims to improve students' mathematics learning outcomes after the application of combination between Out Door and In Door Learning method in Polynomial material using SEPUR SELAM system. This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects in this study are students of class XI IPA 5 of State Senior High School (SMA) 1 Tawangsari in academic year of 2017/2018, consisting of 38 people. The instruments are observation, interviews, and tests. The results reveal that there is an increase in students' mathematics learning outcomes. The success can be obtained from pre-cycle data which shows the average students’ learning outcomes up to 79.026316. In the first cycle, the average of students’ learning outcomes is 84.947, and the second cycle is 90,296053. Based on the acquisition of learning outcomes tests in the second cycle, it is concluded that there is an increase in learning outcomes up to 14.261%. It means that the application of outdoor and indoor method using SEPUR SELAM system can improve mathematics learning outcomes of class XI IPA 5 of SMAN Tawangsari 1 in the academic year of 2017/2018.Keywords: Mathematics Learning Outcomes, SEPUR SELAM.